The effect of state on sensory gating: comparison of waking, REM and non-REM sleep - Kisley, M.A; Olincy, A; Freedman, R (Clinical neurophysiology, 2001)
Objectives: Auditory sensory gating is an electrophysiological assay that has been employed in clinical and basic research to clarify the neurobiological basis of perceptual and attentional impairments associated with schizophrenia and other diseases. In addition to genetically-linked characteristics, this measure also exhibits potentially confounding sensitivity to behavioral state, most notably acute stress. The goal of the present study is to determine if auditory sensory gating of evoked potential component P50 (‘P1’) could be measured during rapid eye movement (REM) sleep, as an alternative to the waking state. Methods: The suppression of vertex-recorded auditory evoked potential components, P30, P50 and N100, was measured as a function of stimulus redundancy using the paired-click paradigm during all-night sleep in 10 control subjects. Average evoked responses were computed separately for 30 min periods of waking, REM sleep, and non-REM (stage 2) sleep. Results: Evoked response component P50 exhibited suppression to the paired-click stimulus during REM sleep, not significantly different than waking. Suppression of wave N100 was significantly poorer during both sleep stages than waking. Component P30 was not suppressed in response to repetitive stimuli under any state of vigilance. Conclusions: In addition to waking, response suppression of evoked potential component P50 can be measured during REM sleep, thus allowing the separation of trait- and state-dependent effects in future investigations of auditory sensory gating.